Synthesis and Evaluation of New Halogenated GR24 Analogs as Germination Promotors for Orobanche cumana - Chen, Yuchao; Kuang, Yi; Shi, Liyang; Wang, Xing; Fu, Haoyu; Yang, Shengxiang; Sampietro, Diego A.; Huang, Luqi; Yuan, Yuan (Frontiers in Plant Science, 2021)
Orobanche and Striga are parasitic weeds extremely well adapted to the life cycle of their host plants. They cannot be eliminated by conventional weed control methods. Suicidal germination induced by strigolactones analogs is an option to control these weeds. Here, we reported two new halogenated (+)-GR24 analogs, named 7-bromo-GR24 (7BrGR24) and 7-fluoro-GR24 (7FGR24), which were synthesized using commercially available materials following simple steps. Both compounds strongly promoted seed germination of Orobanche cumana. Their EC50 values of 1.81×10-8 M (7BrGR24) and 0.90×10-8 M (7FGR24) were 3- and 5-fold lower, respectively, than those of (+)-GR24 and rac-GR24 (EC50 = 5.10-4.98×10-8) (p<0.05). The 7FGR24 was the strongest seed germination promoter tested, with a stimulation percentage of 62.0±9.1% at 1.0×10-8 M and 90.9±3.8% at 1.0×10-6 M. It showed higher binding affinity (IC50 = 0.247 μM) for the strigolactone receptor ShHTL7 than rac-GR24 (IC50 = 0.247 μM), (+)-GR24 (IC50 = 0.319 μM), and 7BrGR24 (IC50 = 0.517 μM). Molecular docking experiments indicated that the binding affinity of both halogenated analogs to the strigolactone receptor OsD14 was similar to that of (+)-GR24. Our results indicate that 7FGR24 is a promising agent for the control of parasitic weeds.